MENUJU ERA RETAIL CERDAS: MEMPERKAYA PENGALAMAN PELANGGAN DAN MENINGKATKAN EFISIENSI OPERASIONAL DENGAN TEKNOLOGI INTERNET OF THINGS (IOT) - Arma Putra, Feby; Susila, Ela; Yulia, Lika; Suheri, Suheri (Desanta Publisher, 2025)
The development of Internet of Things (IoT) technologies has changed the landscape of the retail industry by opening up new opportunities to enrich customer experience and improve operational efficiency. However, the implementation of these technologies in retail management requires an in-depth understanding of their impact on customer experience and operational efficiency. This study aims to explore the implementation of IoT technologies in retail management to enrich customer experience and improve operational efficiency. Quantitative research methods were used with an exploratory and descriptive design. The research population was customers from retail stores that implemented and did not implement IoT, with a sample of 100 people randomly selected. Data were collected through surveys and direct observation at the two selected retail stores. Data analysis used an independent sample t-test to determine significant differences between customer responses in the two types of stores. The findings show that the implementation of IoT in retail management provides an excellent customer experience and improves operational efficiency. The results of the independent sample t-test showed a significant difference between the customer experience at retail stores that implemented IoT and those that did not.